2009
DOI: 10.1073/pnas.0907464106
|View full text |Cite
|
Sign up to set email alerts
|

Planarian Hedgehog/Patched establishes anterior–posterior polarity by regulating Wnt signaling

Abstract: Despite long-standing interest, the molecular mechanisms underlying the establishment of anterior-posterior (AP) polarity remain among the unsolved mysteries in metazoans. In the planarians (a family of flatworms), canonical Wnt/␤-catenin signaling is required for posterior specification, as it is in many animals. However, the molecular mechanisms regulating the posterior-specific induction of Wnt genes according to the AP polarity have remained unclear. Here, we demonstrate that Hedgehog (Hh) signaling is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 37 publications
8
162
2
Order By: Relevance
“…3A). Staining of the regenerants for expression of Dj frizzled-T (DjfzT), a posterior-specific Wnt receptor gene (Yazawa et al, 2009), showed that there was a dramatic reduction of the tissue expressing DjfzT in both Djislet(RNAi) and Djwnt1/P-1(RNAi) (Fig. 3B).…”
Section: Djislet Rnai Causes Tail-less Regeneration Phenotype In Planmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). Staining of the regenerants for expression of Dj frizzled-T (DjfzT), a posterior-specific Wnt receptor gene (Yazawa et al, 2009), showed that there was a dramatic reduction of the tissue expressing DjfzT in both Djislet(RNAi) and Djwnt1/P-1(RNAi) (Fig. 3B).…”
Section: Djislet Rnai Causes Tail-less Regeneration Phenotype In Planmentioning
confidence: 99%
“…Double staining for detection of mRNA expression was performed essentially as described (Yazawa et al, 2009). For the detection of DIG-or fluorescein-labeled RNA probes, samples were incubated with specific antibodies conjugated with alkaline phosphatase or horseradish peroxidase (1:2000; Roche Diagnostics).…”
Section: Whole-mount In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have shown that various growth factors are involved in specifying the body polarity of planarians, such as the antero-posterior and dorsal-ventral axes. Hh (Hedgehog) and Wnt family members induce the differentiation of posterior cells from neoblasts (Gurley et al, 2008;Yazawa et al, 2009). BMP (Bone morphogenetic protein) is involved in dorsal cell specification of neoblasts (Molina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The role of individual genes can be studied using knockdown methods (in vivo RNAi), which can be achieved either through cycles of microinjection or by feeding bacterially-expressed dsRNA constructs 8,9,15 . Both approaches can produce visually striking phenotypes at high penetrance-for example, regeneration of bipolar animals [16][17][18][19][20][21] . To facilitate adoption of this model and implementation of such methods, we showcase in this video article protocols for pharmacological and genetic assays (in vivo RNAi by feeding) using the planarian Dugesia japonica.…”
Section: Introductionmentioning
confidence: 99%